Berta Gleizer Ribeiro e as artes das vidas amazônicas - Lúcia Hussak van Velthem; Bianca Luiza Freire de Castro França; José Ribamar Bessa Freire (Journal de la Société des Américanistes)
This article honors Berta Ribeiro, close to the centenary of her birth, in 2024. The text does not present an in-depth analysis of her contribution to the ethnology of different Brazilian indigenous peoples, given the limitations imposed by a journal article. Rather, it constitutes a celebration of Berta Ribeiro and her work, which contributed to the consolidation of Brazilian and Latin American anthropology. The reflections that follow focus on the approaches to which the anthropologist paid special attention, such as those connected to the study of everyday objects, to Amazonian aesthetics, to the mythology of the indigenous peoples of the upper Rio Negro, and also to ecological issues. Berta Ribeiro’s work provides fruitful connections and dialogues with contemporary anthropology, offering inspiring reflections and practices that reach us in the present.